PBT (Polybutylene Terephthalate) composite material with stable size and preparation method thereof

Through blending and extrusion technology, combined with PBT resin and other additives, a PBT composite material with stable size and post-shrinkage is prepared, which solves the dimensional instability and post-shrinkage problems of existing PBT materials in the automotive gasket field, and achieves high performance and low cost of the material.

CN119735927AActive Publication Date: 2025-04-01DONGGUAN NEW BONDED POLYMER TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411986791.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-01
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

During the use of existing PBT composite materials, there are problems such as unstable dimensionality, low notch impact strength, large molding shrinkage and serious post-shrinkage, which limits their application in the field of automotive gaskets.

Method used

By blending and extruding the PBT resin with an intrinsic viscosity of 0.8-1.2, a commercially available general resin AS resin, a thermoplastic polyester elastomer TPEE with a hardness of 30D-90D, a MBS compatibility agent, ultrafine talc powder and an ethylene acrylic acid-copolymerized sodium salt ionomer, and melt extrusion in a twin screw machine, and dimensionally stable PBT composite material was prepared.

Benefits of technology

The dimensional stability of PBT composite materials is achieved, the post-shrinkage rate is reduced, the physical strength and flexibility of the material are improved, and the toughness requirements of the automotive sealing gasket industry are met. The cost is relatively low and suitable for a wide range of applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005222775990000021
    Figure BDA0005222775990000021
  • Figure BDA0005222775990000071
    Figure BDA0005222775990000071
  • Figure BDA0005222775990000081
    Figure BDA0005222775990000081
Patent Text Reader

Abstract

The invention relates to a PBT (polybutylene terephthalate) composite material with stable size and a preparation method thereof. The PBT composite material with stable size is prepared from the following raw materials in percentage by weight (%): 78-96% of PBT resin, 1-5% of AS (acrylonitrile-styrene) resin, 2-10% of a flexibilizer, 1-5% of a compatilizer, 0.5-2% of an inorganic nucleating agent and 0.1-0.5% of an organic nucleating agent. The preparation method comprises the following steps: weighing the raw materials according to the weight ratio, mixing, adding into a double-screw machine, and carrying out melt extrusion and granulation. Through reasonable formula matching, the obtained PBT composite material can be very stable in size, almost has no post-shrinkage, and has excellent physical and mechanical properties and processability. The automobile sealing gasket is simple in preparation process, low in cost and particularly suitable for being applied to the automobile sealing gasket industry, and has wide application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer materials and relates to a dimensionally stable PBT composite material and a preparation method thereof. Background Art

[0002] PBT, also known as polybutylene terephthalate, is one of the five major engineering plastics. It has high crystallinity, rapid molding, high heat resistance, toughness, fatigue resistance, self-lubrication, low friction coefficient, weather resistance, low water absorption, and various physical properties (including electrical properties) are maintained in a humid environment. It is resistant to hot water, alkalis, acids, and oils, and has good moldability. It is widely used in electrical, electronic, automotive, mechanical instrumentation and other industries as structural parts. The main consumer area of ​​PBT in my country is electronic appliances, mainly for connectors, switches or auto parts. With the rapid development of my country's automotive industry, the demand for PBT is also growing rapidly.

[0003] Gaskets are made of paper, rubber or copper sheets, placed between two planes to strengthen the seal. They are sealing elements set between static sealing surfaces to prevent fluid leakage. In the selection of non-metallic gaskets, rubber is usually used. Due to the excellent processability and oil resistance of PBT, PBT composite materials are currently used to replace rubber gaskets in some automotive sealing gasket fields, which can greatly save costs. However, PBT has problems such as low notch impact strength, large molding shrinkage, and severe post-shrinkage during use, which limits the application of PBT materials in the field of automotive gaskets.

[0004] Therefore, how to make PBT composite materials maintain dimensional stability and basically unchanged post-shrinkage to meet the application needs of downstream manufacturers has always been an urgent problem to be solved in the industry. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a dimensionally stable PBT composite material by a co-extrusion method in view of the above-mentioned defects of the prior art.

[0006] The technical solution adopted by the present invention to solve the technical problem is: to provide a dimensionally stable PBT composite material, which is made of the following raw materials in parts by weight:

[0007]

[0008] In the dimensionally stable PBT composite material of the present invention, the PBT resin has an intrinsic viscosity of 0.8-1.2, preferably a PBT resin with a viscosity of 1.0.

[0009] In the dimensionally stable PBT composite material of the present invention, the AS resin is a commercially available general resin. Only a small amount of the AS resin needs to be added to greatly reduce the initial shrinkage rate of the PBT after demoulding.

[0010] In the dimensionally stable PBT composite material of the present invention, the toughening agent is a thermoplastic polyester elastomer (TPEE) with a hardness of 30D-90D, preferably 50D-70D TPEE. TPEE has good compatibility with PBT resin, can ensure physical strength while increasing resilience and flexibility, meet the toughness requirements of the sealing gasket industry for materials, and has little effect on the crystallization of PBT.

[0011] In the dimensionally stable PBT composite material of the present invention, the compatibilizer is MBS (methyl methacrylate-butadiene-propylene terpolymer). MBS can increase the interfacial compatibility of PBT and AS resin, has good toughening synergy with TPEE, and does not affect the post-shrinkage of the material.

[0012] In the dimensionally stable PBT composite material of the present invention, the inorganic nucleating agent is ultrafine talc powder, preferably talc powder with a mesh size of 5000 or more, and more preferably talc powder with a mesh size of 10000 or more.

[0013] In the dimensionally stable PBT composite material of the present invention, the organic nucleating agent is a sodium salt ionomer of ethylene acrylic acid copolymer. This nucleating agent not only has a high nucleation efficiency, but also has an excellent dispersing effect on ultrafine talc. The compounding of the two nucleating agents can not only greatly improve the crystallinity of the PBT resin, but also improve the crystallization of the PBT, and also effectively prevent the post-crystallization of the material, thereby avoiding the problem of post-shrinkage of the finished product.

[0014] A method for preparing a dimensionally stable PBT composite material comprises the following steps:

[0015] ① Weigh the raw materials according to the aforementioned weight ratio;

[0016] ② Add PBT resin and AS resin into a high-speed mixer and mix for 3-10 minutes, then add TPEE, MBS, ultrafine talcum powder, and sodium salt ionomer of ethylene acrylic acid copolymer and mix for 15-30 minutes;

[0017] ③ The mixture obtained in step ② is placed in a twin-screw machine, melt-extruded, and granulated, wherein the screw aspect ratio is 32-48, and the process conditions are: zone 1 temperature 170-200°C, zone 2 temperature 180-210°C, zone 3 temperature 180-210°C, zone 4 temperature 200-230°C, die head temperature 210-230°C, barrel residence time 0.5-2 minutes, and melt pressure 10-20 MPa.

[0018] The dimensionally stable PBT composite nylon material of the present invention makes full use of the synergistic effect of various additives, not only improves the dimensional stability of the material, but also controls the post-shrinkage with relatively stable means, solving the problem in the industry. It also has excellent comprehensive physical properties and processing properties. Its raw materials are all commercially available, the preparation process is simple, the cost is relatively low, and it can meet various application requirements of dimensionally stable PBT in the market, and is particularly suitable for application in the automotive sealing gasket industry, and has good development prospects. DETAILED DESCRIPTION

[0019] The present invention will be further described below in conjunction with embodiments.

[0020] For the convenience of description, the PBT resin used in the case of the present invention has a trade name of KH2100, which is produced by Kanghui Petrochemical Company; the AS resin has a trade name of A2200NF, which is produced by Ningbo Formosa Chemical Industry Company; the TPEE toughening agent has a trade name of TX636, which is produced by Yizheng Chemical Fiber Company; the MBS compatibilizer has a trade name of EM500, which is produced by LG Company of South Korea; the inorganic nucleating agent ultrafine talc powder has a trade name of HTP-05L, which is produced by Yimifabi Company; the organic nucleating agent has a trade name of AClyn285P, which is produced by Honeywell Company.

[0021] Example 1.

[0022] Put 92.7% PBT resin and 1.5% AS resin by weight into a mixing barrel for premixing for 7 minutes, then add 3% TPEE TX636, 2% EM500, 0.6% talcum powder HTP-05L and 0.2% AClyn285P, and stir for 20 minutes. Then put the mixed materials into a twin-screw extruder for melting, mixing, extrusion, and granulation. The screw diameter of the twin-screw extruder is 35mm, the ratio of screw length to diameter is set to 32, the extrusion temperature is 180℃ for zone 1, 230℃ for zone 2, 200℃ for zone 3, 220℃ for zone 4, the head temperature is 230℃, the residence time is 0.5-2min, and the pressure is 15MPa.

[0023] Example 2.

[0024] Put 89.7% PBT resin and 2% AS resin by weight into a mixing barrel for premixing for 8 minutes, then add 5% TPEE TX636, 2% EM500, 1% talcum powder HTP-05L and 0.3% AClyn285P, and stir for 22 minutes. Then put the mixed materials into a twin-screw extruder for melting, mixing, extrusion and granulation. The screw diameter of the twin-screw extruder is 50mm, the ratio of screw length to diameter is set to 36, the extrusion temperature is 190℃ for zone 1, 235℃ for zone 2, 230℃ for zone 3, 210℃ for zone 4, the head temperature is 225℃, the residence time is 1-1.5min, and the pressure is 13MPa.

[0025] Example 3.

[0026] Put 87.7% PBT resin and 3% AS resin by weight into a mixing barrel for premixing for 4 minutes, then add 5% TPEE TX636, 3% EM500, 1% talcum powder HTP-05L and 0.3% AClyn285P, and stir for 25 minutes. Then put the mixed materials into a twin-screw extruder for melting, mixing, extrusion and granulation. The screw diameter of the twin-screw extruder is 65mm, the ratio of screw length to diameter is set to 40, the extrusion temperature is 195℃ for zone 1, 230℃ for zone 2, 235℃ for zone 3, 220℃ for zone 4, the head temperature is 220℃, the residence time is 1-2min, and the pressure is 16MPa.

[0027] Example 4.

[0028] Put 83.1% PBT resin and 3% AS resin by weight into a mixing barrel for premixing for 5 minutes, then add 5% TPEE TX636, 3% EM500, 1.5% talcum powder HTP-05L and 0.4% AClyn285P, and stir for 26 minutes. Then put the mixed materials into a twin-screw extruder for melting, mixing, extrusion, and granulation. The screw diameter of the twin-screw extruder is 75mm, the ratio of screw length to diameter is set to 44, the extrusion temperatures are 195℃ for zone 1, 230℃ for zone 2, 235℃ for zone 3, 220℃ for zone 4, the die head temperature is 220℃, the residence time is 1-2min, and the pressure is 13MPa.

[0029] Example 5.

[0030] Put 81.8% PBT resin and 4% AS resin by weight into a mixing barrel for premixing for 7 minutes, then add 8% TPEE TX636, 4% EM500, 1.8% talcum powder HTP-05L and 0.4% AClyn285P, and stir for 28 minutes. Then put the mixed materials into a twin-screw extruder for melting, mixing, extrusion, and granulation. The screw diameter of the twin-screw extruder is 52mm, the ratio of screw length to diameter is set to 40, the extrusion temperature is 190℃ for zone 1, 230℃ for zone 2, 235℃ for zone 3, 215℃ for zone 4, the head temperature is 225℃, the residence time is 1-1.5min, and the pressure is 19MPa.

[0031] Example 6.

[0032] Put 78.5% PBT resin and 4% AS resin by weight into a mixing barrel for premixing for 5 minutes, then add 10% TPEE TX636, 5% EM500, 2% talcum powder HTP-05L and 0.5% AClyn285P, and stir for 30 minutes. Then put the mixed materials into a twin-screw extruder for melting, mixing, extrusion and granulation. The screw diameter of the twin-screw extruder is 40mm, the ratio of screw length to diameter is set to 48, the extrusion temperature is 190℃ for zone 1, 230℃ for zone 2, 235℃ for zone 3, 210℃ for zone 4, the head temperature is 230℃, the residence time is 0.5-2min, and the pressure is 17MPa.

[0033] Comparative example 1.

[0034] Add 5% TPEE TX636, 3% EM500, 1% talcum powder HTP-05L and 0.3% AClyn285P to 90.7% PBT resin by weight, and stir for 25 minutes. Then put the mixed materials into a twin-screw extruder for melting, mixing, extrusion and granulation. The screw diameter of the twin-screw extruder is 65mm, the ratio of screw length to diameter is set to 40, the extrusion temperature is 195℃ for zone 1, 230℃ for zone 2, 235℃ for zone 3, 220℃ for zone 4, the head temperature is 220℃, the residence time is 1.5-2min, and the pressure is 16MPa.

[0035] Comparative example 2.

[0036] Put 92.7% PBT resin and 3% AS resin by weight into a mixing barrel for premixing for 5 minutes, then add 3% EM500, 1% talcum powder HTP-05L and 0.3% AClyn285P, and stir for 25 minutes. Then put the mixed materials into a twin-screw extruder for melting, mixing, extrusion, and granulation. The screw diameter of the twin-screw extruder is 52mm, the ratio of screw length to diameter is set to 40, the extrusion temperature is 195℃ for zone 1, 230℃ for zone 2, 235℃ for zone 3, 220℃ for zone 4, the head temperature is 220℃, the residence time is 1-1.5min, and the pressure is 15MPa.

[0037] Comparative example 3.

[0038] Put 90.7% PBT resin and 3% AS resin by weight into a mixing barrel for premixing for 5 minutes, then add 5% TPEE TX636, 1% talcum powder HTP-05L and 0.3% AClyn285P, and stir for 26 minutes. Then put the mixed materials into a twin-screw extruder for melting, mixing, extrusion and granulation. The screw diameter of the twin-screw extruder is 52mm, the ratio of screw length to diameter is set to 40, the extrusion temperature is 190℃ for zone 1, 220℃ for zone 2, 235℃ for zone 3, 220℃ for zone 4, the head temperature is 220℃, the residence time is 0.5-2min, and the pressure is 14MPa.

[0039] Comparative example 4.

[0040] Put 90.7% PBT resin and 3% AS resin by weight into a mixing barrel for premixing for 5 minutes, then add 5% TPEE TX636, 3% EM500, 0.3% AClyn285P and stir for 22 minutes. Then put the mixed materials into a twin-screw extruder for melting, mixing, extrusion and granulation. The screw diameter of the twin-screw extruder is 35mm, the ratio of screw length to diameter is set to 32, the extrusion temperatures are 190℃ for zone 1, 215℃ for zone 2, 235℃ for zone 3, 220℃ for zone 4, the die head temperature is 220℃, the residence time is 1-2min, and the pressure is 13MPa.

[0041] Comparative example 5.

[0042] Put 89% PBT resin and 3% AS resin by weight into a mixing barrel for premixing for 5 minutes, then add 5% TPEE TX636, 3% EM500, 1% talcum powder HTP-05L and stir for 24 minutes. Then put the mixed materials into a twin-screw extruder for melting, mixing, extrusion and granulation. The screw diameter of the twin-screw extruder is 75mm, the ratio of screw length to diameter is set to 36, the extrusion temperature is 195℃ for zone 1, 215℃ for zone 2, 235℃ for zone 3, 220℃ for zone 4, the head temperature is 215℃, the residence time is 1-1.5min, and the pressure is 14MPa.

[0043] The PBT composite materials prepared in the first six embodiments and five comparative examples were tested, and the performance evaluation method and implementation standard were as follows:

[0044] The granulated material was dried in a blast oven at 110°C for 3 to 6 hours, and then the dried material was injection molded on an injection molding machine to prepare samples, and the injection molding mold temperature was controlled at 80°C. The tensile strength test was carried out according to ASTM D638, with a sample size of 180×12.7×3.2mm and a tensile speed of 50mm / min; the bending performance test was carried out according to ASTM D790, with a sample size of 128×13×3.2mm, a bending speed of 3mm / min, and a span of 64mm; the cantilever beam impact strength was carried out according to ASTM D256, with a sample size of 63.5×12.7×4.2mm, and a notch size of one-fifth of the sample thickness. The melt index was carried out according to ASTM D1238, with the test conditions of 250 degrees and a 2.16 kg weight.

[0045] The shrinkage test was carried out according to ASTM D955 standard. The baked particles were directly injection molded in a mold with 5 18×5mm spline molds. The spline length was measured with a vernier caliper and repeated three times. The maximum and minimum values ​​of the single product diameter range were taken. The shrinkage rate can be calculated as (mold length-spline length)*100% / mold length. After two weeks, the previous spline length was tested again to calculate the shrinkage rate and compare it with the previous shrinkage rate.

[0046] The comprehensive mechanical properties of the embodiments and comparative examples were evaluated by testing the tensile strength, flexural strength, impact strength, melt index and shrinkage rate. The results are shown in Tables 1 and 2.

[0047] Table 1 Example formulation and performance

[0048]

[0049] Table 2 Comparative Example Formula and Performance

[0050]

[0051] It can be seen from Examples 1-6 that the PBT composite material of the present invention has good physical properties, small shrinkage rate of molding size, and the shrinkage remains basically unchanged after two weeks.

[0052] From Comparative Example 1, it can be seen that AS resin has a great influence on both the initial shrinkage and the post-shrinkage of the material. From Comparative Examples 2-5, it can be seen that the PBT composite material not only has a large shrinkage, but also has a certain post-shrinkage after 2 weeks, which is not as good as the effect of the embodiment, indicating that the materials and additives selected in the present invention have a good synergistic effect in preventing post-shrinkage, and neither of them can be missing.

[0053] In summary, the dimensionally stable PBT composite material prepared by the present invention perfectly solves the problem of large post-shrinkage rate of PBT in the application of automotive sealing gaskets. Its raw materials are all commercially available, the preparation process is simple, the cost is relatively low, and it is particularly suitable for use in the automotive gasket industry, and has good development prospects.

[0054] The above is a detailed introduction to a dimensionally stable PBT composite material and a preparation method provided by the present invention. The principles and implementation methods of the present invention are described in detail using specific examples. The description of the above examples is only used to help understand the method and core idea of ​​the present invention. At the same time, for those skilled in the art, according to the idea of ​​the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as limiting the present invention.

Claims

1. A dimensionally stable PBT composite material, characterized in that: Made from the following raw materials in parts by weight:

2. The dimensionally stable PBT composite material according to claim 1, characterized in that: The PBT resin is a PBT raw material resin with an intrinsic viscosity of 0.8 to 1.

2.

3. The dimensionally stable PBT composite material according to claim 1, characterized in that: The AS resin is an acrylonitrile-styrene copolymer.

4. The dimensionally stable PBT composite material according to claim 1, characterized in that: The toughening agent is thermoplastic polyester elastomer (TPEE).

5. The dimensionally stable PBT composite material according to claim 1, characterized in that: The compatibilizer is MBS (methyl methacrylate-butadiene-propylene terpolymer).

6. The dimensionally stable PBT composite material according to claim 1, characterized in that: The inorganic nucleating agent is ultrafine talc.

7. The dimensionally stable PBT composite material according to claim 1, characterized in that: The organic nucleating agent is a sodium salt ionomer of ethylene acrylic acid copolymer.

8. A dimensionally stable PBT composite material according to claim 1, characterized in that: The following steps are involved: ① Weigh the raw materials according to the aforementioned weight ratio; ② Add PBT resin and AS resin into a high-speed mixer and mix for 3-10 minutes, then add TPEE, MBS, ultrafine talcum powder, and sodium salt ionomer of ethylene acrylic acid copolymer and mix for 15-30 minutes; ③ The mixture obtained in step ② is placed in a twin-screw machine, melt-extruded, and granulated, wherein the screw aspect ratio is 32-48, and the process conditions are: zone 1 temperature 170-200°C, zone 2 temperature 180-210°C, zone 3 temperature 180-210°C, zone 4 temperature 200-230°C, die head temperature 210-230°C, barrel residence time 0.5-2 minutes, and melt pressure 10-20 MPa.

Citation Information

Patent Citations

  • Viscosity increased recovery poly-ester and preparation process of it composite material

    CN100999606A

  • Low-warpage halogen-free flame-retardant glass fiber reinforced PBT / AS alloy and preparation method thereof

    CN104693701A

  • High-crystallization rate PBT resin and preparation method thereof

    CN105440266A

  • Low-temperature-impact resistant polyester composition and preparation method thereof

    CN108034204A

  • Low warp polybutylene terephthalate molding compositions

    US20060030659A1